Drag Reduction of AL-Ahdab Crude Oil Using Chemical Additives - Subkh, Talib M.; Hussein, Hussein Q. (Journal of Petroleum Research and Studies, 2022)
The viscosity of crude oil has a crucial role in drag reduction during pipeline transportation; hence additives are required to enhancing the flow properties of AL-Ahdab crude oil. In this work, the potato starch biopolymer and CTAB surfactant are utilized to achieve the target. The drag reduction experiments were carried out at different crude oil flow rates (20-35-50 liters/min), pipe diameters (0.5-0.75 -1 inch), and different concentrations of potato starch (500-2000 ppm) and CTAB (100-500 ppm). The results showed that these additives had minimized flow resistance in various operating conditions, the drag reduction percent increased with increasing of additives concentration increase. The maximum drag reduction achieved using CTAB and potato starch is 41.6% and 36.3%, respectively, at 50 liters/min and 1-inch pipe diameter.